Use of effective contraception following provision of the progestogen-only pill for women presenting to community pharmacies for emergency contraception (Bridge-It): a pragmatic cluster-randomised crossover trial. Issue 10262 (14th November 2020) - Cameron, Sharon T; Glasier, Anna; McDaid, Lisa; Radley, Andrew; Baraitser, Paula; Stephenson, Judith; Gilson, Richard; Battison, Claire; Cowle, Kathleen; Forrest, Mark; Goulao, Beatriz; Johnstone, Anne; et al.
Summary: Background: Unless women start effective contraception after oral emergency contraception, they remain at risk of unintended pregnancy. Most women in the UK obtain emergency contraception from community pharmacies. We hypothesised that pharmacist provision of the progestogen-only pill as a bridging interim method of contraception with emergency contraception plus an invitation to a sexual and reproductive health clinic, in which all methods of contraception are available, would result in increased subsequent use of effective contraception. Methods: We did a pragmatic cluster-randomised crossover trial in 29 UK pharmacies among women receiving levonorgestrel emergency contraception. Women aged 16 years or older, not already using hormonal contraception, not on medication that could interfere with the progestogen-only pill, and willing to give contact details for follow-up were invited to participate. In the intervention group, women received a 3-month supply of the progestogen-only pill (75 μg desogestrel) plus a rapid access card to a participating sexual and reproductive health clinic. In the control group, pharmacists advised women to attend their usual contraceptive provider. The order in which each pharmacy provided the intervention or control was randomly assigned using a computer software algorithm. The primary outcome was the use of effective contraception (hormonal or intrauterine) at 4 months. This study is registered, ISRCTN70616901 (complete). Findings: Between Dec 19, 2017, and June 26, 2019, 636 women were recruited to the intervention group (316 [49·6%], mean age 22·7 years [SD 5·7]) or the control group (320 [50·3%], 22·6 years [5·1]). Three women (one in the intervention group and two in the control group) were excluded after randomisation. 4-month follow-up data were available for 406 (64%) participants, 25 were lost to follow-up, and two participants no longer wanted to participate in the study. The proportion of women using effective contraception was 20·1% greater (95% CI 5·2–35·0) in the intervention group (mean 58·4%, 48·6–68·2), than in the control group (mean 40·5%, 29·7–51·3 [adjusted for recruitment period, treatment group, and centre]; p=0·011).The difference remained significant after adjusting for age, current sexual relationship, and history of effective contraception use, and was robust to the effect of missing data (assuming missingness at random). No serious adverse events occurred. Interpretation: Provision of a supply of the progestogen-only pill with emergency contraception from a community pharmacist, along with an invitation to a sexual and reproductive health clinic, results in a clinically meaningful increase in subsequent use of effective contraception. Widely implemented, this practice could prevent unintended pregnancies after use of emergency contraception. Funding: National Institute for Health Research (Health Technology Assessment Programme project 15/113/01).